Trends and variability of water balance components over a tropical savanna and Eucalyptus forest in Australia. Issue 2 (11th December 2021) - Kang, Yinhong; Zhang, Lu; Dawes, Warrick
Abstract: In this paper, the long-term dynamics of water balance components in two different contrasting ecosystems in Australia were simulated with an ecohydrological model (WAter Vegetation Energy and Solute modelling (WAVES)) over the period 1950–2015. The selected two ecosystems are woodland savanna in Daly River and eucalyptus forest in Tumbarumba. The WAVES model was first manually calibrated and validated against soil water content measured by cosmic-ray probe and evapotranspiration measured with eddy flux techniques. The calibrated model was then used to simulate long-term water balance components with observed climate data at two sites. Analyzing the trends and variabilities of potential evapotranspiration and precipitation is used to interpret the climate change impacts on ecosystem water balance. The results showed that the WAVES model can accurately simulate soil water content and evapotranspiration at two study sites. Over the period of 1950–2015, annual evapotranspiration at both sites showed decreasing trends (−1.988 mm year −1 in Daly and −0.381 mm year −1 in Tumbarumba), whereas annual runoff in Daly increased significantly (5.870 mm year −1 ) and decreased in Tumbarumba (–0.886 mm year −1 ). It can be concluded that the annual runoff trends are consistent with the rainfall trends, whereas trends in annual evapotranspiration are influenced by both rainfall and potential evapotranspiration. The results can provide evidence for controlling the impacting factors for different ecosystems under climate change. HIGHLIGHTS: This study highlights the importance of long-term climatic variability in evaluating water balance components at different vegetation ecosystems. The manually calibrated ecohydrological model is adopted in this paper.